Green concepts through shape-grammar – the language of intermediate spaces in traditional Malay houses / Suzana Said ... [et al.] - Suzana, Said; M. Sabrizaa, Abdul Rashid; Rosmawati, Mohamed; Neta Suredah, Baharum; Izatul Asyikin, Nordin (2015)
The traditional Malay houses (TMH) can be seen as an embodiment of a true implementation of green architecture through its design efficiency and moderation in the use of resources throughout the lifecycle of the houses. This paper describes the relationship of green architecture to the language of the intermediate spaces of the TMH as part of the general analysis of traditional Malay houses from the sustainability or “green” perspective. The research is conducted by examining the shape grammar descriptions of the intermediate spaces and relating them with the green concept from design to construction stages. From the design perspective, the intermediate spaces introduce efficient natural ventilation and lighting to the main house, while from the construction perspective, the development of the intermediate spaces promote efficient and timely use of timber materials in its construction.